The Role of Satellite Channels in Imparting Behavior to Children from the Point of View of their Parents in Tulkarm City (Journal Of Educational and Psychological Researches, 2022)
This study aims to identify the role of satellite channels in imparting behavior to children from the point of view of their parents in Tulkarm city. The researcher used a descriptive technique. A sample of (18000) males and females married couples was used above 20 years old in the city of Tulkarm. The study sample size is (201) married couples. It took place in September 2020. The questionnaire was the main tool for collecting data. The study found that the total degree of satellite channels contribution in imparting negative behaviors to children was high, as it reached (72.20%). The total degree of the role of satellite channels in imparting positive behaviors to children was medium, reaching (69.20%). Moreover, the results also indicated that there were no statistically significant differences in the role of satellite channels in shifting behavior to children from their parent's point of view in Tulkarm, due to differences in gender, age, and educational qualification.